EFEKTIVITAS KURIKULUM LEMBAGA PENDIDIKAN ISLAM DALAM MEMBENTUK PERILAKU SOSIAL SISWA - Miftakhul Rohman; Anang Darun Naja; A. Fikri Amiruddin Ihsani; Doni Saputra (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
This research examines the process of forming social behavior in Islamic educational institutions in urban Blitar. This research examines the process of forming social behavior through the curriculum of Islamic educational institutions in urban Blitar and how the curriculum of Islamic educational institutions effectively shapes the social behavior of students in urban Blitar. To answer the problem formulation, researchers used qualitative research methods with data collection techniques in the form of observation, interviews and documentation. This method was chosen to obtain detailed and comprehensive research data regarding the process of forming social behavior in Islamic educational institutions in the Blitar urban area. The data obtained was then presented descriptively and analyzed using the Talcotts-Parsons structure-function theory. The findings show that Islamic educational institutions can influence social behavior both inside and outside the classroom. In class we incorporate social behavior education values ​​from the Ministry of Education and Culture. Meanwhile, from outside the classroom, instilling religious values ​​in students, encouraging students to live in a good social environment, instilling the values ​​of discipline and independence, and maximizing social interaction between students. Teach using exemplary methods, customs and instructions. Apart from that, as a form of social awareness, Friday Welas Asih activities are carried out to provide support to fellow students and build friendship. The effectiveness of the Islamic Education Institute curriculum in shaping the social behavior of Blitar urban students is in line with the religious, social and cultural values ​​that develop in society.